2021
DOI: 10.1111/jora.12694
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sense of Belonging and Family Structure in Adolescent Adjustment

Abstract: The present study adopted an ecological perspective, and examined effects of sense of belonging to multiple contexts in relation to adolescent adjustment, as well as possible differences between adolescents from intact and divorced families. Self‐report questionnaires were used to investigate perceptions of family, school, peer, and neighborhood belonging among 969 adolescents. Results showed that mean level differences in belonging exist based on family structure, and that levels of family and neighborhood be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…Construct validity was supported by several studies that used the balanced relatedness scale as an indicator of autonomy support and examined associations with adolescents’ problem behaviors (e.g., Van der Giessen et al, 2014 ). The results of those studies indicated that higher scores of autonomy support were related to higher scores on sense of family belonging (Rejaän et al, 2022 ), and adolescents’ educational identity (van Doeselaar et al, 2016 ). Moreover, lower scores on autonomy support were related to more internalizing and externalizing problems (Vrolijk et al, 2020 ) and depressive symptoms (van der Giessen et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Construct validity was supported by several studies that used the balanced relatedness scale as an indicator of autonomy support and examined associations with adolescents’ problem behaviors (e.g., Van der Giessen et al, 2014 ). The results of those studies indicated that higher scores of autonomy support were related to higher scores on sense of family belonging (Rejaän et al, 2022 ), and adolescents’ educational identity (van Doeselaar et al, 2016 ). Moreover, lower scores on autonomy support were related to more internalizing and externalizing problems (Vrolijk et al, 2020 ) and depressive symptoms (van der Giessen et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Another key factor in adolescents' development is experiencing a sense of belonging: feeling connected to parents and having a secure base from which they can explore the world (Ryan & Deci, 2000;Griffin et al, 2017). Compared to their peers from intact families, adolescents from divorced families are prone to experience a weaker sense of belonging to their families (King et al, 2018;Rejaän et al, 2021a). Within post-divorce families, research has also demonstrated differences in the extent to which adolescents experience a sense of belonging to maternal and paternal households, which could partially be explained by the generally unequal amount of time that adolescents typically spend with their mothers versus their fathers (Rejaän et al, 2021a).…”
Section: Experiences Of Autonomy and Belonging In Divorced Familiesmentioning
confidence: 99%
“…As such, a lack of autonomy may become apparent through the feeling of having no say in decisions about living arrangements and related aspects in their daily living situation (Friendly & Grolnick, 2009). Another major consequence of parental divorce is that it usually puts pressure on the quality of parent-child and interparental relationships (Amato, 2010;Friendly & Grolnick, 2009), which may become apparent through a reduced sense of family belonging (Rejaän et al, 2021a). Thus far, studies have examined the role of parents in adolescents' sense of autonomy and belonging, mostly in intact families.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents who experience positive peer relationships tend to have healthier self-esteem, experience positive psychosocial adjustment (Savin- Williams & Berndt, 1990), and are more likely to avoid violence and delinquency (Pardini et al, 2012). Adolescents who struggle to form positive connections with peers experience elevated symptoms of loneliness (De Luca et al, 2022;Rejaän et al, 2022), contributing to depression and suicidality (Prinstein et al, 2000). Past research suggests that adolescents' peer experiences link to mental health outcomes, educational consequences, addictive behaviors, and mortality decades later (Allen et al, 2014;Almquist & Östberg, 2013;Menting et al, 2016;Modin et al, 2011).…”
Section: Peer Connectednessmentioning
confidence: 99%